Utilization of silicon dioxide nanoparticles in foam enhanced oil recovery - A comprehensive review - Latif, W.M.S.M. (Institute of Physics Publishing, 2019)
In recent years, the development of nanotechnology has paved the way of using nanoparticles as foam stabilizer. The applications of silicon dioxide (SiO 2 ) nanoparticles in improving foam stability received great attention among researchers over the past decade, either synergistic SiO 2 nanoparticles-surfactant foam or nanoparticles-gas supercritical foam. In fact, the significant difference between nanoparticles and surfactant as foam stabilizer is the adsorption energy of nanoparticles at gas-liquid interfaces, which are hundred or thousand times bigger than surfactant adsorption energy. Besides, the effectiveness of nanoparticles as foam stabilizer also influenced by the maximum capillary pressure, particle arrangement during film drainage, and the presence of aggregate and cork formation inside lamellae. Variety parameters of nanoparticles-fluid-rock properties have been studied in order to optimize foam flooding efficiency-e.g., type of nanoparticles, particle concentration, particle size, surface modification, salinity, permeability, wettability etc. However, to date, no attempt has been made to comprehensively review these existing literatures. Thus, to fill this identified gap, the results of previous studies are discussed, challenged and direction for further studies are suggested in this paper. Â© Published under licence by IOP Publishing Ltd.